The Stability of Nonlinear Differential Systems with Random Parameters - Josef Diblík; Irada Dzhalladova; Miroslava Růžičková (Abstract and Applied Analysis)
The paper deals with nonlinear differential systems with random parameters in a general form. A new method for construction of the Lyapunov functions is proposed and is used to obtain sufficient conditions for L2-stability of the trivial solution of the considered systems.